A characterisation of elite open water swimmers' core temperature responses and preparation practices in European Aquatics competitions - Markey, K.; Christmas, B. C. R.; Esh, C.; Galan-Lopez, N.; Adams, W. M.; Constantini, N.; Mountjoy, M. L.; Taylor, L. (Journal of Science and Medicine in Sport, 2026)
Objectives Open water swimming competition occurs within a water temperature (Tw) range (World Aquatics Tw: 16-31°C) where heat- (hyperthermia) and cold-related (hypothermia) medical events and race-dropouts regularly occur. These can be attributed to the thermodynamic properties of water and human thermoregulatory (Treg) maladaptations for submersion [modest deviations (±0.5-2°C) in core temperature (Tc) can impair performance and health]. Additionally, little real-world knowledge regarding elite open water swimmer preparation [e.g., heat/cold acclimation/acclimatisation] for extreme environments is available. Thus, elite swimmers' Tc and preparation practices were characterised during open water swimming competition. Design (i) Characterise Tc responses; and (ii) questionnaire preparation practices of elite swimmers within cold and warm Tw European Aquatics open water swimming competitions. Methods Tc data were characterised (ingestible-telemetry) for 50 (20 female) elite swimmers during the 2023-25 European Aquatics Open Water Swimming Cup (Leg 4 — COLD1, Leg 1 — COLD2, Leg 5 — COLD3, Leg 1 — COLD4) and the 2023 Junior European Aquatics Open Water Swimming Championships (WARM). A pre- and post-race questionnaire was disseminated to survey training/preparation practices and symptomology in-race. Results Tc responses were highly variable [maximum±Tc °C change: COLD1 (+1.2°C; -2.0°C), COLD2 (+1.2°C; -1.6°C), COLD3 (+1.7°C; -1.3°C), COLD4 (+2.2°C; -4.2°C), WARM (+1.8°C; -1.7°C)]. Mild and/or hypo/hyper-thermia co-presented within the same race. Tc in-race was not associated with race time, nor ranking (P>=.080). Heat/cold acclimation/acclimatisation adoption was not associated with lower likelihood of hypo-/hyper-thermia (P>=.184), nor cold/heat-related symptomology in-race (P>=.837). Conclusions The observed variability in Tc responses, alongside co-presentation of mild and/or hyper-/hypo-thermia in-race surfaces the challenges to protect open water swimmers' health and performance during competition. Whilst heat/cold acclimation/acclimatisation and body temperature manipulation (e.g., cooling/heating) interventions may be helpful, there is a paucity of open water swimming specific data to evidence-inform practice.